Antisense and / or Immunostimulatory Oligonucleotide Therapeutics - Agrawal, S.; Kandimalla, E.R. (Current Cancer Drug Targets, 2001)
Antisense technology, which is based on a simple and rational principle of Watson-Crick complementary base pairing of a short oligonucleotide with the targeted mRNA to downregulate the disease-causing gene product, has progressed tremendously in the last two decades. Antisense oligonucleotides targeted to a number of cancer-causing genes are being evaluated in human clinical trials. While the first-generation phosphorothioate antisense oligonucleotides are in clinical trials, a number of factors, including sequence motifs that could lead to unwanted mechanisms of action and side effects, have been identified. The severity of the side effects of first-generation antisense oligonucleotides is mostly dependent on the presence of certain sequence motifs, such as CpG dinucleotides. A number of second-generation chemical modifications have been proposed to overcome the limitations of the first-generation antisense oligonucleotides. The safety and efficacy of several second-generation mixed-backbone antisense oligonucleotides are being evaluated in clinical trials. The immune stimulation affects observed with CpG-containing antisense oligonucleotides are being exploited as a novel therapeutic modality, with several CpG oligonucleotides being evaluated in clinical trials. A number of medicinal chemistry studies performed to date suggest that the immunomodulatory activity of CpG oligonucleotides can be fine-tuned by site-specific incorporation of chemical modifications in order to design disease-specific oligonucleotide therapeutics
Keywords: Antisense